Comparative Safety Profiles of Anti-Amyloid Therapies in Early Alzheimer’s Disease (AD): A Detailed Systematic Review and Meta-Regression Analysis of Amyloid Related Imaging Abnormalities (ARIA) – Incidence and Infusion Reactions for Lecanemab, Donanemab, and Aducanumab - Sathyan Soundara Rajan; Sneh Babhulkar; Gaurav Uppal; Sharmi Bhattacharyya; Asha Devi Dhandapani (BJPsych Open)
Aims: Alzheimer’s disease continues to be a huge health concern around the globe. Although similar recent developments in anti-amyloid therapy are promising, there is concern about some side effects like ARIA. The purpose of this meta-analysis was to systematically review and compare the safety characteristics of three of the most promising anti-amyloid drugs: lecanemab, donanemab and aducanumab, specifically, the frequency of ARIA-E (oedema) and ARIA-H (haemorrhage).